High-Throughput Sequencing for Understanding the Ecology of Emerging Infectious Diseases at the Wildlife-Human Interface - Titcomb, Georgia C.; Jerde, Christopher L.; Young, Hillary S. (Frontiers in Ecology and Evolution, 2019)
Rising rates of emerging infectious diseases (EIDs) demand creative, efficient, and integrative investigations to understand their transmission, ecological contingencies, and dynamics at wildlife-human interfaces. High-throughput sequencing (HTS) methodologies provide enormous potential to unravel these contingencies to improve our understanding, but their potential is only just starting to be realized. While recent work has largely focused on novel pathogen discovery at likely interfaces, high-throughput methods can also allow disease ecologists to better explore the critical effects of climate, seasonality, and land-use changes on EIDs. HTS can facilitate the creation of entire host-pathogen networks, integrate important microbiome and co-infection data, and even pinpoint important exposure routes at interfaces through environmental media. Here we highlight studies at the frontier of HTS and disease ecology research, identify current limitations, and outline promising future applications for EIDs.